2019
DOI: 10.1093/ofid/ofz274
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Lipoglycopeptides: “Lineless Antibiotics” for Serious Infections in Persons Who Use Drugs

Abstract: Background Injection drug use is associated with serious infections. Due to challenges with medical management of addiction, relapses and additional infections are common. Persons who use drugs (PWUD) are more likely to leave against medical advice before completing treatment, which could result in treatment failure. Prolonged intravenous (IV) antimicrobial therapy in PWUD may be complicated by concern for IV catheter misuse, sometimes requiring prolonged hospitalization. Ideal alternatives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…The oritavancin package insert lists similar adverse effects, with the addition of phlebitis and tachycardia at 2.5% 4 . In clinical trials, both agents showed a similar incidence of infusion‐related reactions; however, at our institution, rates of such reactions were higher with oritavancin 39 . With respect to serious adverse events (AEs)—which is of particular interest given the extra‐long half‐life of these agents—researchers reported that among 1778 enrolled patients in the dalbavancin group within phase II/III of the drug's ABSSSI clinical development program, 328 (18.4%) experienced treatment‐related AEs, 3 (0.2%) were serious treatment‐related AEs (compared with 9/1224 (0.7%) in the comparator group), and the duration of all treatment‐emergent AEs was similar (not longer) to the duration observed with the short‐acting comparators, despite dalbavancin's log half‐life 55 .…”
Section: Considerations For Selection Of Dalbavancin Versus Oritavancinmentioning
confidence: 58%
See 4 more Smart Citations
“…The oritavancin package insert lists similar adverse effects, with the addition of phlebitis and tachycardia at 2.5% 4 . In clinical trials, both agents showed a similar incidence of infusion‐related reactions; however, at our institution, rates of such reactions were higher with oritavancin 39 . With respect to serious adverse events (AEs)—which is of particular interest given the extra‐long half‐life of these agents—researchers reported that among 1778 enrolled patients in the dalbavancin group within phase II/III of the drug's ABSSSI clinical development program, 328 (18.4%) experienced treatment‐related AEs, 3 (0.2%) were serious treatment‐related AEs (compared with 9/1224 (0.7%) in the comparator group), and the duration of all treatment‐emergent AEs was similar (not longer) to the duration observed with the short‐acting comparators, despite dalbavancin's log half‐life 55 .…”
Section: Considerations For Selection Of Dalbavancin Versus Oritavancinmentioning
confidence: 58%
“…In yet another study, a savings of $1752.46–$6475.87/patient were projected with avoidance of hospitalization by administering oritavancin in the emergency departments 42 . Favorable real‐world experiences with the use of dalbavancin, including a report of significant cost savings, have recently been reported by a group of authors from Spain, and similar findings were corroborated by a U.S.‐based group in two retrospective studies evaluating both agents (savings of €3000/patient [~$3400/patient], $17,000/patient, and up to $40,000/patient in PWUD, in the three studies, respectively) 38,39,44 …”
Section: Economic Rationale For Transition From Inpatient To Outpatiementioning
confidence: 70%
See 3 more Smart Citations